KETERAMPILAN SISWA MENULIS KARANGAN ARGUMENTASI - Endah, Revina; Wartiningsih, Agus; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Â AbstractThe research entitled Argument Writing Student Skills aims to train students to convey their ideas or opinions on a matter that is equipped with facts. The formulation of the problem in this study includes the suitability of the content of the argument with the topic, the completeness of the content expressed in the essay of argumentation, the accuracy of the facts used, and the purpose of convincing the reader. Sources of data in this study were students of class XII AP 1 of SMK 1 Pontianak Academic Year 2015/2016 which amounted to 26 students, men amounted to 2 people and women amounted to 24 people. The data in this study are the results of essay arguments in the form of compatibility with the characteristics of the argumentation. Data collection techniques used in this study are indirect communication techniques. The data collection tool in this study is a question sheet. The validity of the data carried out by the author is persistence of observation, peer examination through discussion, and triangulation of investigators.Â  The results of the research and data analysis can be concluded as follows first the suitability of the content of the argument with the topic there are 19 students who have written arguments according to the topic. Second, on the part of completing the content of the argumentation there are 3 students describing the contents of the argument completely. Third, in the section on the accuracy of the facts there are 2 students including facts. Fourth, in the purpose of convincing the reader there are 2 students describing arguments that are very convincing to the reader.Keywords: Writing, Argument Essay